1982
DOI: 10.1139/b82-070
|View full text |Cite
|
Sign up to set email alerts
|

Tremorgenic indole metabolites and aflatoxins in sclerotia of Aspergillus flavus: an evolutionary perspective

Abstract: Isolates of Aspergillus flavus Link from both cool and warm latitudes were cultured on potato dextrose agar containing yeast extract to identify sclerotia-producing strains. Chloroform–MeOH extracts of sclerotia were analyzed for the presence of aflatoxins and major indole metabolites (e.g., cyclopiazonic acid, aflatrem, and dihydroxyaflavinine). Aflatoxin is reported from sclerotia of A. flavus for the first time. Cyclopiazonic acid was detected primarily in sclerotia of isolates from warmer latitudes. Aflatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…The species were predominantly isolated from soil, crop fields, nuts, figs and insects which might correlate with the hypothesized insecticide properties of aflatoxins and STs (Gloer et al 1988;Wicklow & Cole 1982 2), with branch lengths calculated using the average pathway method (see p. 132 in (Nei & Kumar 2000)) and are in the units of the number of changes over the whole sequence. Nidulantes in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species were predominantly isolated from soil, crop fields, nuts, figs and insects which might correlate with the hypothesized insecticide properties of aflatoxins and STs (Gloer et al 1988;Wicklow & Cole 1982 2), with branch lengths calculated using the average pathway method (see p. 132 in (Nei & Kumar 2000)) and are in the units of the number of changes over the whole sequence. Nidulantes in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…than aflatoxins (13 spp.). Despite 50 y of intensive research, the ecological function of ST and aflatoxin has never been elucidated; however, these toxins have, often in synergy with other toxic extrolites, been demonstrated to be active against fungivorous insects probably as chemical protection for conidia and sclerotia (Gloer et al 1988;Matsumura & Knight 1967;Ohtomo et al 1975;Wicklow & Cole 1982). ST biosynthesis is coupled to conidiation, and might improve fungal fitness for survival (Wilkinson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of AFs may occur in both conidia and sclerotia of A. flavus. Increased animal toxicity has been attributed to the combined activity of AFs and other metabolites present in sclerotia (42). Sclerotia are proposed by some researchers to be a vestige of the sexual structures termed cleistothecia produced by Aspergillus spp.…”
mentioning
confidence: 99%
“…Warm humid conditions also favor the development of some maize diseases in the tropics and subtropics (Ahuja and Payak 1981). Aspergillus flavus isolates that produce aflatoxins and cyclopiazonic acid are more frequently recovered from warmer regions, suggesting that geographic variation in selection pressure has impacted the distribution ratio of these fungal toxins (Manabe and Tsuruta 1978;Wicklow 1990;Wicklow and Cole 1982). Dihydroresorcylide displayed phytotoxic activity in a maize leaf needle wound assay (Poling et al 2008) but showed no activity (MIC > 50 µg/mL) against fungal endophytes and pathogens of maize.…”
Section: Discussionmentioning
confidence: 99%